HUBUNGAN AKTIVITAS FISIK DENGAN FUNGSI KOGNITIF LANSIA DI POSBINDU WILAYAH KABUPATEN BANDUNG BARAT - Niknik Nursifa (Jurnal Infokes, 2021)
According to United Nation Population Division, Department of Economic and Social Affairs, the number of elderly (≥ 60 year-old) will be over the number of children population (0-14 year-old) for the first time in history. The number of elderly in West Bandung districtfrom 2017 data is 78,277 people, and those who are over 70 year-old is around 52,911 people. Through survey, it was found that the number of those who suffer from cognitive disorders from 9 villages in West Bandung district is 365 elderly aged over 60 year-old. This research was aimed at studying and explaining the correlation between physical activities with cognitive functions in elderly at Posbindu, West Bandung district, in year 2018. Qualitative design with cross sectional study was employed. Moreover, the number of the participants was 53 elderly. The data was obtained through questionnaires and interviews. The findings revealed that there is a meaningful correlation between physical activities (p-value =0.0014) with cognitive functions in elderly. It can be summed up that the dominant factor is age. It means that the older the age, their risk would be 12 times of suffering from cognitive disorders.